INHIBISI PERTUMBUHAN BAKTERI Salmonella spesies sv abony DAN Bacillus cereus OLEH INFUSA BIJI ADAS (Foeniculum vulgare) - N.W. Dewi; Tatang Sopandi (FMIPA : Universitas PGRI Adi Buana, 2014)
The study of inhibition activity of fennel seeds ( Foeniculum vulgare ) was conducted on Salmonella species sv abony and Bacillus cereus. Fennel seeds heated at 900C for 15 min and made concentration 0; 0.147; 1.47; 147 g/l by dilution in water. This study found concentration of fennel seed infusion significant (P< 0.05) effect on count and growth rate of Salmonella species sv abony and Bacillus cereus. Lowest count and growth of S. abony and B. cereus was obtained in 147 g/l concentration of fennel seed infusion. Keywords : fennel seeds, Salmonella spesies sv abony, Bacillus cereus.